Analisis Pengendalian Kualitas Produk Cover 012 dalam Mengurangi Jumlah Cacat Produk Menggunakan Metode Seven Tools di Pt Sinergi Pari Jaya Abadi - Candra, Adi; Nugroho, Rendra Bagus Sapto; Taufik, Agus (Jurnal Optimalisasi, 2025)
This study discusses defect control, focusing on the identification and handling of defects in various sectors, such as industry. The aim of the research is to analyze the main causes of defects and evaluate the control strategies that have been implemented. Using a data-driven approach and analytical methodology, this study provides recommendations to improve the effectiveness of defect control, minimize its impact, and create more integrated policies. The research results are expected to contribute to the development of more targeted company policies in reducing defects in various fields. PT Sinergi Pari Jaya Abadi, a company engaged in the production of various products, including Cover 012 products, faces challenges in maintaining consistent quality. One of the main issues faced by the company is the high defect rate in Cover 012 products, which affects increased production costs, reduced efficiency, and decreased customer satisfaction. This research aims to analyze the quality control of Cover 012 products at PT Sinergi Pari Jaya Abadi using the Seven Tools method. The study uses descriptive and qualitative methods with a Seven Tools approach to identify the root causes of product defects and propose improvements. The results show that the most dominant defect is NG Over Taping, accounting for 62.16% of the total identified defects. Fishbone Diagram analysis indicates that the causes of product defects include human, machine, and material factors. Proposed improvements include regular calibration to ensure machines continue to operate according to specifications, improving communication between the design, production, and QC teams to ensure a shared understanding of product sizes, and implementing a periodic inspection system during the taping process to detect errors early